2019
DOI: 10.1111/vco.12560
|View full text |Cite
|
Sign up to set email alerts
|

The adrenergic receptor antagonists propranolol and carvedilol decrease bone sarcoma cell viability and sustained carvedilol reduces clonogenic survival and increases radiosensitivity in canine osteosarcoma cells

Abstract: Adrenergic receptor (AR) expression has been demonstrated at several sites of primary and metastatic tumour growth and may influence proliferation, survival, metastasis and angiogenesis. AR antagonists like propranolol and carvedilol inhibit proliferation, induce apoptosis and synergize with chemotherapy agents in some cancers. Radiation resistance is mediated in many cells by upregulation of pro‐survival pathways, which may be influenced by ARs. Studies evaluating AR antagonists combined with radiation are li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 88 publications
0
15
0
Order By: Relevance
“…Increased antitumor activity as a result of combining PPN with cytotoxic agents was previously reported in non-OSA preclinical and clinical studies, in which addition of repurposed drug to paclitaxel-, 5-FU-or even CDDP-based chemotherapy increased antiangiogenic and antiproliferative effects of monotherapies, as well as decreased distant metastases in patients [30,37,38]. Moreover, it was recently reported that β-blockade in different bone sarcoma models, increases sensitivity to radiotherapy, especially in canine OSA [24]. In our in vivo protocol sustained treatment with PPN, alone and especially in addition to CDDP, caused a marked decrease in OSA tumor progression, showing that PPN may complement chemotherapy, increasing its effectiveness without overt toxicity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Increased antitumor activity as a result of combining PPN with cytotoxic agents was previously reported in non-OSA preclinical and clinical studies, in which addition of repurposed drug to paclitaxel-, 5-FU-or even CDDP-based chemotherapy increased antiangiogenic and antiproliferative effects of monotherapies, as well as decreased distant metastases in patients [30,37,38]. Moreover, it was recently reported that β-blockade in different bone sarcoma models, increases sensitivity to radiotherapy, especially in canine OSA [24]. In our in vivo protocol sustained treatment with PPN, alone and especially in addition to CDDP, caused a marked decrease in OSA tumor progression, showing that PPN may complement chemotherapy, increasing its effectiveness without overt toxicity.…”
Section: Discussionmentioning
confidence: 81%
“…As recently reported, expression of β-ARs and several catecholamines, including norepinephrine, was signi cantly higher in OSA in comparison to healthy bone [21]. In addition, all subtypes of β-AR were found to be expressed in a wide collection of human and canine OSA or other bone sarcoma models [22][23][24], making the exploration of non-selective β-blocker PPN in OSA an appealing niche for further studies. Considering the unsatis ed clinical needs of OSA and the multiple reported bene ts of PPN as a broad antitumor agent, the aim of the present study was to evaluate the in vitro/in vivo antitumoral activity of PPN in OSA, as a monotherapy or in combination with metronomic chemotherapy.…”
Section: Introductionmentioning
confidence: 66%
“…Enhancement of antineoplastic activity as a result of combining PPN with cytotoxic agents was previously reported for other tumor types, in which addition of repurposed drug to chemotherapy increased antiangiogenic and antiproliferative effects of monotherapies, as well as decreased distant metastases in patients [57][58][59] . Moreover, it was recently reported that β-blockade increases sensitivity to radiotherapy in different bone sarcoma models, especially in canine OSA 17 . In our in vivo protocol, sustained treatment with PPN using validated human equivalent doses (10 mg/kg/day i.p.…”
Section: Discussionmentioning
confidence: 98%
“…Although sympathetic nervous system (SNS) activation and catecholamine-triggered signaling pathways are deeply involved in cancer initiation and growth 15 , little is known about the specific role of β-adrenergic signaling in OSA progression. Interestingly, expression of catecholamines and their receptors was previously reported in multiple human and canine OSA models 16,17 . Moreover, norepinephrine and β-adrenergic receptors were also detected in OSA clinical samples, showing increased expression levels in comparison to matched non-oncological healthy bone 18 , making the exploration of β-blocker PPN in OSA an appealing niche for further studies.…”
mentioning
confidence: 90%
“…Included in this issue are reviews aimed at understanding the clinical and pathological course of sarcomas by refining histologic classification and improving or standardizing histologic margin assessment of sarcomas . Original research manuscripts investigating the basic biology of sarcoma cells include studies evaluating the effects of toceranib phosphate in vitro and in vivo and a potential role for adrenergic receptor antagonists in moderating radiosensitivity . Yet another manuscript builds on previous data and identifies the interaction between RUNX2 and core‐binding factor beta as a potential target in osteosarcoma cells .…”
mentioning
confidence: 99%